Trends in Postmodern Landscape Creations: From Deconstructed Space to Augmented Space—The Cases of Tschumi and Hahm - Kamoun, Sami (Environmental Science & Sustainable Development, 2026)
This study aims to explore the notion of landscape by analyzing its various spatial and aesthetic expressions through the lens of two postmodern architectural trends: deconstructivism and parametricism. From a theoretical standpoint, these two movements oppose the rigidity of modernism while developing fundamentally distinct conceptual approaches: one is rooted in philosophical reflection, whereas the other privileges a technological approach. However, research on this issue remains limited, particularly in the fields of landscape and garden design. In this context, the study is based on the analysis of two emblematic projects: the Parc de la Villette, designed by Bernard Tschumi and completed in Paris in 1987, and the installation Augmented Grounds by Soomeen Hahm Design, developed in Canada in 2020. The adopted methodology relies on an in-depth literature review, complemented by a visual analysis based on photographic and video materials. The first project, conceived at the landscape scale, implements a spatial deconstruction based on the superposition of points—the folies—, a system of lines structuring circulation, and surfaces defining green and recreational spaces. The second project, at the architectural scale, presents itself as a landscaped playground composed of an assembly of ropes, combining a craft-based weaving technique with parametric precision enabled by the use of augmented reality. Through this comparative perspective, the study examines the notion of landscape in light of these two major yet distinct postmodern movements. It aims to identify the spatial forms, aesthetics, philosophical foundations, and technologies mobilized in these projects, as well as to highlight their similarities, differences, and respective contributions to the field of landscape and garden design.